JCircus 2.0: Uma extensão da ferramenta de tradução de Circus para Java - Barrocas, Samuel Lincoln Magalhães (2011)
This dissertation aims at extending the JCircus tool, a translator of formal specifications into code that receives a Circus specification as input, and translates the specification into Java code. Circus is a formal language whose syntax is based on Z s and CSP s syntax. JCircus generated code uses JCSP, which is a Java API that implements CSP primitives. As JCSP does not implement all CSP s primitives, the translation strategy from Circus to Java is not trivial. Some CSP primitives, like parallelism, external choice, communication and multi-synchronization are partially implemented. As an aditional scope, this dissertation will also develop a tool for testing JCSP programs, called JCSPUnit, which will also be included in JCircus new version. The extended version of JCircus will be called JCircus 2.0.